The Effect of Teaching Approaches on the Pattern of Pupils' Cognitive Structure: Some Evidence from the Field - (:unkn) unknown (DE LA SALLE UNIV-MANILA, 2009)
In this study, the effect of different teaching approaches on pupils' cognitive structures (N=110) in the topic of circulation system was investigated by using the Word Association Test (WAT). WAT was administered as a pre-test and post-test to all groups. The control group was taught by lecturing. In addition to lecturing, concept maps were used in the first experimental group and the cooperative learning approach was used in the second experimental group. In order to map the pupils' cognitive structures, response frequencies in the WAY were used. The results showed that: i) pupils generated more response words for the majority of the key words in the post-WAT than they did in the pre-WAT; and ii) there was not any observable difference in the pre-WAT mind maps of all the groups in terms of complexity and branching. However, the post-WAT mind maps clearly showed considerable difference regarding complexity and branching. In other words, the teaching approach may seem to affect the associations between concepts in the pupils' minds. Implications of the results for better teaching and meaningful learning are critically discussed.
Keywords: Word association test; teaching approaches; cognitive structure; circulation system; WORD-ASSOCIATION TESTS; CONCEPT MAPS; CONCEPTUAL CHANGE; CHEMISTRY; STUDENTS; SCIENCE; KNOWLEDGE; EDUCATION; GENETICS